The Effect of Kaizen Implementation on Employee Performance and its Implications on After-Sales Service Productivity at PT Tunas Toyota Gatot Subroto - Imam Khoirudin; Gurawan Dayona Ismail; Asti Nur Aryanti; Ridlwan Muttaqin; Recky Recky (Eduvest - Journal of Universal Studies, 2026)
The Indonesian automotive industry faces increasingly intense competition, making operational excellence in after-sales services a critical determinant of customer satisfaction and organizational sustainability. Despite the widespread adoption of continuous improvement practices, many authorized dealerships continue to experience challenges, including service completion delays, inefficient resource utilization, and inconsistent productivity levels. This study aimed to examine the effect of Kaizen implementation on employee performance and its implications for after-sales service productivity at PT Tunas Toyota Gatot Subroto. A quantitative research design with descriptive and verification approaches was employed. The study involved 60 employees from the after-sales division selected through purposive sampling. Data were analyzed using SPSS 25 for descriptive statistics and SmartPLS 3 for structural equation modeling, including validity, reliability, and hypothesis testing. The findings showed that Kaizen implementation had a positive and significant effect on employee performance, while employee performance significantly improved after-sales service productivity. However, Kaizen implementation did not directly affect productivity; instead, employee performance served as a significant mediating variable linking Kaizen implementation to productivity improvement. The structural model demonstrated strong explanatory power, indicating that Kaizen contributed substantially to improving employee performance, which subsequently enhanced productivity. The study concluded that successful Kaizen implementation should be supported by continuous employee development, active employee participation, and performance improvement initiatives to maximize after-sales service productivity. These findings contribute to the continuous improvement literature by highlighting the mediating role of employee performance in the relationship between Kaizen implementation and operational productivity within the automotive after-sales service sector.